The obligations to protect of the occupying powers in Iraq according to international law - Christian Schaller (Stiftung Wissenschaft und Politik (SWP), 2003)
After the attack on the UN headquarters in Baghdad on August 19, UN SecretaryGeneral Kofi Annan told press that the United Nations had been aware of the dangerous situation in Iraq. At the same time the UN also had hoped that the occupying powers, the United States and the United Kingdom, would take the necessary precautions to enable the UN staff in Iraq to exercise their mandate in a safe environment. This comment raises the fundamental question of the nature and extent of the protection duties of an occupying power under international law.(SWP Comments / SWP)
Keywords: 320